Exon 5 Polymorphisms in the O6-Alkylguanine DNA Alkyltransferase Gene and Lung Cancer Risk in Non–Smokers Exposed to Second-Hand Smoke - Cohet, Catherine; Borel, Stephane; Nyberg, Fredrik; Mukeria, Anush; Brüske-Hohlfeld, Irene; Constantinescu, Vali; Benhamou, Simone; Brennan, Paul; Hall, Janet; Boffetta, Paolo (Cancer epidemiology, biomarkers & prevention, 2004)
Purpose: The objective of the study was to examine the association of three exon 5 variants in the O 6 -alkylguanine DNA alkyltransferase (AGT) gene involved in the repair of the mutagenic DNA lesion O 6 -alkylguanine formed by nitrosamines, with lung cancer risk in never-smokers. Experimental Design: Exon 5 of the AGT gene was sequenced in genomic DNA from 136 cases and 133 hospital- or population-based controls for whom questionnaire information on second-hand smoke and diet was available to determine the frequencies of the Gly 160 Arg, Ile 143 Val, and Lys 178 Arg variant alleles. Results: No codon 160 Arg variant alleles were found in the study population. The codon 143 Val and 178 Arg variant alleles, present at allele frequencies of 0.07, showed 100% linkage. The odds ratio (OR) of lung cancer for these variant carriers was 2.05 [95% confidence interval (CI) 1.03–4.07]. The risk varied between the different lung cancer pathologies with an increased risk for adenocarcinoma (OR 2.67, 95% CI 1.21–5.87) or small cell carcinoma (OR 4.83, 95% CI 0.91–25.7) but not for squamous cell carcinoma (OR 1.07, 95% CI 0.27–4.18). Compared with individuals carrying the mutant alleles unexposed to second-hand smoke, the OR for exposed variant carriers was 1.95 (95% CI 0.53–1.15); a similar interaction, although not significative, was observed for low consumption of cruciferous vegetables and for green vegetables and tomatoes. Conclusions: These results point toward a role of AGT polymorphisms in lung cancer susceptibility among never-smokers, in particular among subjects exposed to environmental carcinogens.